Persepsi Dosen dan Karyawan Universitas Islam Negeri Ar-Raniry Terhadap Murabahah Bank Syariah - Ismuadi I; Nevi Hasnita; Muhammad Al Harits (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Murabahah financing is a financing product that dominates the distribution of financing funds in Islamic banks. This study aims to determine the perceptions of lecturers and employees of FEBI UIN Ar-Raniry on murabahah financing at Islamic banks in Aceh. This research belongs to the type of descriptive qualitative research with primary data collection (through the distribution of interview questions) to lecturers and employees of FEBI UIN Ar-Raniry. The results of this study indicate that as many as 59.1% of participants stated that the mechanism and implementation of murabahah financing contracts in Islamic banking in Aceh was in accordance with sharia principles